PA.04 Effects of additional lay support for pregnant women with social risk factors on antenatal attendance and maternal psychological health: a randomised controlled trial (ELSIPS). (9th June 2014) - Kenyon, S; Jolly, K; Hemming, K; Ingram, L; Blissett, J; Dann, S; Lilford, R; MacArthur, C
Abstract : Background: Maternal, perinatal and child health outcomes appear worse in families with social risk factors. The current increase in use of lay support in this area lacks evidence. Methods: Following routine midwife systematic assessment of social risk factors nulliparous women were randomly assigned to standard maternity care or the addition of referral to a Pregnancy Outreach Worker (POW) service. Primary outcomes were Edinburgh Postnatal Depression Scale 1 (EPDS) 8–12 weeks postpartum and antenatal visits attended. Pre-specified powered subgroup comparisons were among women with two or more social risks. Results: 662 women were randomly assigned to standard maternity care and 662 to addition of the POW service. The incidence of postnatal depression (defined as an EPDS ≥ 12) was reduced by 6% overall (relative risk (RR) 0.72 (0.55, 0.93) P = 0.01) and by 6% in the pre-specified subgroup. (RR 0.72(0.53, 0.98) P = 0P = 0.04) Results were consistent if a more stringent EPDS cut off is used. The mean EPDS improved overall (MD –0.59 [–1.24, 0.06]) and significantly in the subgroup ((MD –0.79 [–1.56, -0.02]). Maternal infant bonding was significantly improved. Antenatal attendances were high in the standard care control and did not increase further with the addition of the intervention (10.1 vs. 10.1 (mean difference (MD) –0.00, 95% CI [–0.37, 0.37]). Conclusions: The provision of lay support to women with identified social risk factors has a modest effect on maternal mental health, particularly among women with more social risk: given known effects of maternal depression on child outcomes, this may be of major importance for society. Reference: Cox JL, Holden JM, Sagovsky R. Detection of postnatal depression. Development of the 10 item postnatal depression scale. Br J Psychiatry 1987;150:782–6